Penanaman Pendidikan Karakter Peduli Lingkungan Dengan Konsep Bebayaan Etam (Gotong Royong) Pada Siswa SLB Negeri Tenggarong - Ratna Khairunnisa; Tri Cahyo Nugroho (SISTEMA: Jurnal Pendidikan, 2022)
Character education is one of the efforts to national development goals and instill personality or morals that are guided by Pancasila values. The purpose of this research is to describe the application of instilling the character of caring for the environment in Tenggarong State SLB students which focuses on the concept of bebayaan etam (gotong-royong). This study uses a qualitative method with a descriptive approach. Data collection was carried out by observing the implementation of bebayaan etam activities at the Tenggarong State SLB which leads to the formation of a caring character for the environment. Data analysis was carried out using the qualitative data analysis model of Miles and Huberman, including data collection, data reduction, data presentation, and drawing conclusions.